2015
DOI: 10.1111/nph.13524
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic moss stress assessment based on chlorophyll content and leaf density retrieved from imaging spectroscopy data

Abstract: SummaryThe health of several East Antarctic moss-beds is declining as liquid water availability is reduced due to recent environmental changes. Consequently, a noninvasive and spatially explicit method is needed to assess the vigour of mosses spread throughout rocky Antarctic landscapes. Here, we explore the possibility of using near-distance imaging spectroscopy for spatial assessment of moss-bed health.Turf chlorophyll a and b, water content and leaf density were selected as quantitative stress indicators. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 71 publications
0
45
0
1
Order By: Relevance
“…The original digital number ( DN ) values were converted to relative reflectance. The calibration equation was as follows [27]: Reftarget=DNtargetDNnoiseDNpanelDNnoise×Refpanel where DN target , DN noise and DN panel refer to the DN value of target, electronic noise and reference panel, respectively. Ref target and Ref panel refer to the reflectance value of target and reference panel, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The original digital number ( DN ) values were converted to relative reflectance. The calibration equation was as follows [27]: Reftarget=DNtargetDNnoiseDNpanelDNnoise×Refpanel where DN target , DN noise and DN panel refer to the DN value of target, electronic noise and reference panel, respectively. Ref target and Ref panel refer to the reflectance value of target and reference panel, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As many recent studies have proved, laboratory measurements of leaf optical properties in the visible and infrared regions are a valuable technique for understanding different plant physiological processes and stress detection [1,2,3,4,5], as well as photosynthesis efficiency evaluation, energy balance calculation, global terrestrial net primary productivity modelling [6,7,8,9] or vegetation stress detection [10,11,12,13,14]. Despite its wide applications, significant measurement uncertainties and knowledge gaps exist.…”
Section: Introductionmentioning
confidence: 99%
“…Malenovský et al. () demonstrated that this approach is transferable from standardized laboratory spectral measurements to ground‐based Antarctic moss hyperspectral images of matching wavelengths acquired at different field locations. This study scales the approach further to airborne (UAS) and WorldView‐2 (WV2) satellite spectral imagery.…”
Section: Methodsmentioning
confidence: 99%
“…We used the epsilon‐SVR training optimization technique with the nonlinear Gaussian radial basis function (RBF) kernel to estimate Cab and ELD as described in Malenovský et al. (). The laboratory reflectance measurements of moss canopies, acquired in 2013 and 1999 with a sampling interval of 1 nm, were first convolved in bandwidths and spectral sampling intervals of WV2 and micro‐Hyperspec sensors in accordance with their specific spectral response functions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation